Chronic Pain, Loss, and Suffering : A Clinical Perspective - Roy, R. (Ranjan) (Book collections on Project MUSE., 2004)
"Loss and grief are an inherent part of chronic illness. But while much has been written on grief associated with death and dying, the grief and losses accompanying chronic illness have received relatively little scholarly attention. In this book, Ranjan Roy addresses the complex issues related to loss among those with chronic illness." "In Chronic Pain, Loss, and Suffering, Roy evaluates the current state of knowledge through an examination of contemporary literature and clinical application. He presents a series of comprehensive case studies, which together indicate that the key challenge for many patients is loss of self-esteem and control. The chapters deal with a range of losses such as job loss, declining ability to function, loss of family and sexual role, old age and its related losses, and suicide. Through discussion of the struggles and successes that chronically ill patients encounter in their journey, this work will assist clinicians in helping patients come to terms with the difficulties they face and to establish a renewed sense of self."--Jacket